Establishment method affects rice root plasticity in response to drought and its relationship with grain yield stability - Xie, Xiaobing; Quintana, Marinell R.; Sandhu, Nitika; Subedi, Sushil R.; Zou, Yingbin; Rutkoski, Jessica Elaine; Henry, Amelia (Oxford University Press, 2021)
By responding to the variable soil environments in which they are grown, the roots of rice crops are likely to contribute to yield stability across a range of soil moistures, nutrient levels, and establishment methods. In this study, we explored different approaches to quantification of root plasticity and characterization of its relationship with yield stability. Using four different statistical approaches (plasticity index, slope, AMMI, and factor analytic) on a set of 17 genotypes including several recently-developed breeding lines targeted to dry direct-seeding, we identified only very few direct relationships between root plasticity and yield stability. However, genotypes identified as having combined yield stability and root plasticity showed higher grain yields across trials. Furthermore, root plasticity was expressed to a greater degree in puddled transplanted trials rather than under dry direct-seeding. Significant interactions between nitrogen and water resulted in contrasting relationships between nitrogen-use efficiency and biomass stability between puddled-transplanted and direct-seeded conditions. These results reflect the complex interaction between nitrogen, drought, and even different types of drought (as a result of the establishment method) on rice root growth, and suggest that although rice root plasticity may confer stable yield across a range of environments, it might be necessary to more narrowly define the targeted environments to which it will be most beneficial.